Tumor Necrosis Factor Inhibition and Parkinson Disease: A Mendelian Randomization Study. (23rd March 2021) - Kang, Xiaoying; Ploner, Alexander; Pedersen, Nancy L.; Bandres-Ciga, Sara; Noyce, Alastair J.; Wirdefeldt, Karin; Williams, Dylan M.
Abstract : Objective: To evaluate the effects of long-term tumor necrosis factor (TNF) inhibition on the risk and age at onset of Parkinson disease (PD), we performed a 2-sample Mendelian randomization study using genome-wide association studies (GWAS) summary statistics. Methods: Genetic variants in the vicinity of TNFRSF1A, the gene encoding TNF receptor 1 (TNFR1), were identified as predictive of pharmacologic blockade of TNFR1 signaling by anti-TNF therapy, based on genetic associations with lower circulating C-reactive protein (CRP; GWAS n = 204, 402). The effects of TNF-TNFR1 inhibition were estimated for PD risk (ncases /controls = 37, 688/981, 372) and age at PD onset (n = 28, 568) using GWAS data from the International Parkinson's Disease Genomics Consortium and 23andMe, Inc. To validate variants as proxies of long-term anti-TNF treatment, we also assessed whether variant associations reflected anticipated effects of TNFR1 inhibition on Crohn disease, ulcerative colitis, and multiple sclerosis risk (n = 38, 589-45, 975). Results: TNF-TNFR1 signaling inhibition was not estimated to affect PD risk (odds ratio [OR] per 10% lower circulating CRP = 0.99; 95% confidence interval [CI] 0.91–1.08) or age at onset (0.13 years later onset; 95% CI −0.66 to 0.92). In contrast, genetically indexed TNF-TNFR1 signaling blockade predicted reduced risk of Crohn disease (OR 0.75; 95% CI 0.65–0.86) and ulcerative colitis (OR 0.84; 95% CI 0.74–0.97) and increased multiple sclerosis risk (OR 1.57; 95% CI 1.36–1.81). Findings were consistent across models using different genetic instruments and Mendelian randomization estimators. Conclusions: Our findings do not imply that TNF-TNFR1 signaling inhibition will prevent or delay PD onset. Classification of Evidence: This study provides Class II evidence that TNF-TNFR1 signaling inhibition is not associated with the risk or age at onset of PD.